A Qualitative Study of Recruitment Barriers, Motivators, and Community-Based Strategies for Increasing Clinical Trials Participation among Rural and Urban Populations. Issue 5 (May 2015) - Friedman, Daniela B.; Foster, Caroline; Bergeron, Caroline D.; Tanner, Andrea; Kim, Sei-Hill
Purpose: Participation in clinical trials (CTs) is low among rural communities. Investigators report difficulty recruiting rural individuals for CTs. The study purpose was to identify recruitment barriers, motivators, and strategies to help increase access to and participation in CTs in rural and urban communities. Approach: Qualitative focus groups/interviews. Setting: Rural and urban counties in one southeastern state. Participants: Two hundred twelve African-American and white men and women ages 21+. Method: Nineteen focus groups and nine interviews were conducted. Audio files were transcribed and organized into NVivo10. Recurring themes were examined by geographic location. Results: Although similar barriers, motivators, and strategies were reported by urban and rural groups, perceptions regarding their importance varied. Recruitment barriers mentioned in both rural and urban groups included fear, side effects, limited understanding, limited time, and mistrust. Rural groups were more mindful of time commitment involved. Both rural and urban participants reported financial incentives as the top motivator to CT participation, followed by personal illness (urban groups) and benefits to family (rural groups). Recruitment strategies suggested by rural participants involved working with schools/churches and using word of mouth, whereas partnering with schools, word of mouth, and media were recommended most by urban groups. Conclusion: Perceived recruitment barriers, motivators, and strategies did not differ considerably between rural and urban groups. Major barriers identified by participants should be addressed in future CT recruitment and education efforts. Findings can inform recruitment and communication strategies for reaching both urban and rural communities.